Oocyte Development and Loss - Gosden, Roger G. (Seminars in Reproductive Medicine, 2013)
Soon after implantation, cell lineages bifurcate into future somatic and germ cells. Canonical expression of germ cell–specific genes continues during and after their migration to the gonadal ridge, where, after further cell cycles, they enter meiosis, form syncytial clusters, and arrest at diplotene for folliculogenesis. The balance between cell survival and death leaves an ovarian follicular reserve as a legacy.
Keywords: age; follicle; germ cell; oocyte; ovarian reserve